Co-contracting for creative–business collaboration - Hietanen-Kunwald, Petra; Haapio, Helena; Isohanni, Perttu; Falay, Zeynep; Vyas, Rupesh (Aalto-yliopisto, 2026)
This article conceptualizes co-contracting as a narrative and adaptive design process that leads to a co-created contract – a co-contract – functioning as a shared script for collaboration and goal-achievement. Rather than starting from pre-existing templates, co-contracting begins with the co-creation of a shared plot that articulates the purpose, expectations, and trajectory of the collaboration. Focusing on collaborations between creatives and businesses, the article argues that effective contracting requires more than legal enforceability. Co-contracting is framed around three pillars: building relationships and trust, enabling collaborative sense-making, and ensuring fairness. Information design is suggested as a tool for the operationalization of the concept.
Keywords: co-contracting; trust-building; collaborative sensemaking; fairness; information design; fi=Talousoikeus|en=Business Law|